The development of realistic mathematics education-based student worksheets to enhance higher-order thinking skills and mathematical ability - Sri Sutarni; Sutama Sutama; Harun Joko Prayitno; Anam Sutopo; Pasttita Ayu Laksmiwati (Jurnal Infinity, 2024)
This study aims to provide educational resources in the form of worksheets based on Realistic Mathematics Education (RME) principles and focus on the topic of equal fractions. The main criteria for these resources are validity, feasibility, and effectiveness. The development methodology employed in this study is the ADDIE model, which encompasses the Analysis, Design, Development, Implementation, and Evaluation stages. The participants of this study consisted of 14 pupils enrolled in class IV at SDM Alam Surakarta. The assessment tools employed consisted of assessments on student learning outcomes about equivalent fractions and supplementary materials in the form of questionnaires, interview guides, and observation sheets. The examination of the data reveals that the learning tools have achieved a high level of validity, falling inside the extremely valid category, with an average score of 4.26. The feasibility test for the LKS, conducted by the assisting instructor, yielded an average score of 4.4. The pupils' performance on the LKS assessment yielded an average score of 4.89, placing them in the "very feasible" category. The classical student learning outcomes achieved a completeness of 85.71%, as evidenced by an average score of 80.35. Notably, 12 students attained a complete score. There is a noticeable upward trend in student engagement during each learning session. The findings from the data analysis conducted on instructors' competencies in managing RME-based learning revealed an average score of 92, indicating a high level of proficiency. Students who were qualitatively integrated into the eligibility questionnaire also expressed positive responses. Therefore, learning tools based on Realistic Mathematics Education (RME) exhibit high validity, feasibility, and effectiveness in educational settings, as they have been empirically demonstrated to enhance students' mathematical proficiency.